FAKTOR KUALITAS LAYANAN SERTA PENGARUHNYA TERHADAP KEPUASAN DAN LOYALITAS NASABAH PERBANKAN DI AMBON - Debby Likumahua (Journal of Business & Banking, 2011)
The purpose of this study is to assess the factors considered by the customers in perceivingthe quality of bank services in Ambon as well as examine the influence of service quality oncustomer satisfaction and loyalty as well as to test the effect of bank customers satisfactionin Ambon. Analysis tool used is the first factor analysis. This is for assessing the quality factorsof bank services. The second is the linear regression used to test whether the effect onservice quality and satisfaction whether satisfaction influences customer loyalty in Ambon.This research was carried out in Ambon in five major banks namely Bank Mandiri, BankRakyat Indonesia, Bank Negara Indonesia, Bank Central Asia and Bank CIMB Niaga. Thesample used in this research consists of 147 respondents. The result shows that there are fourfactors considered by the customers in Ambon in perceiving the quality of service. These factorsare the reliability, assurance, tangibles, and empathy. Furthermore, simultaneous servicequality influence customer satisfaction in Ambon and customer satisfaction is partially abanking customer loyalty in Ambon